Fish invading deserts: non‐native species in arid Moroccan rivers. Issue 1 (12th September 2014) - Clavero, Miguel; Esquivias, Javier; Qninba, Abdeljebbar; Riesco, María; Calzada, Javier; Ribeiro, Filipe; Fernández, Néstor; Delibes, Miguel
Abstract Desert rivers are highly dynamic systems in which dry periods, frequently involving the cessation of superficial flow, alternate with violent flash floods. In spite of their territorial importance and high functional and biological diversity, desert rivers have received little attention in the scientific literature, especially in Northern Africa. This study investigated the distribution of non‐native fish, their relationship with river damming and their potential impacts on native biodiversity in the main river basins draining arid areas of Morocco (Oued Draa, Oued Ziz and Oued Ghir), based on field sampling covering 84 stream reaches. Thirteen fish species were recorded, eight of which are non‐native. Two species (stone moroko, Pseudorasbora parva, and bleak, Alburnus alburnus) had not been previously recorded in Morocco, while the native sandsmelt (Atherina boyeri) had not been cited as an invader. Pumpkinseed (Lepomis gibbosus) was the most widely distributed non‐native fish. Non‐native fish species were associated with reservoirs, colonizing the regulated downstream reaches. In contrast, unregulated upstream reaches tended to be free of non‐natives. The low abundance of native fish in reservoirs seems to be caused by the impacts of introduced fish species. Management options for environmental flow are limited, owing to reduced water availability. Non‐native fish management should thus focus on limiting the spread of species already introduced and avoiding new introductions, especially into reservoirs. Copyright © 2014 John Wiley & Sons, Ltd.